2019
DOI: 10.1016/j.hpb.2018.06.1797
|View full text |Cite
|
Sign up to set email alerts
|

Recipient obesity does not affect survival after deceased donor liver transplantation for hepatocellular carcinoma. A national retrospective cohort study in the United States

Abstract: Background: The oncological effects of obesity on liver transplant (LT) patients with hepatocellular carcinoma (HCC) remains unclear. We investigated patient overall survival and tested two-way interactions between donor and recipient obesity status. Methods: Using the UNOS database, a total of 8352 LT recipients with HCC were included. Donors and recipients were stratified in normal weight (NW), overweight (OW) and obese (OB). Hazard ratios (HR) for any cause of death and interactions between recipient and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…This is in line with the finding of previous studies [32]. Further, BMI was not found to be associated with outcomes of HCC patients after liver transplantation neither in present nor previous studies [51]. The necessity of evaluating subcutaneous and visceral adipose tissue on computed tomography in obese patients seems more controversial, as there was only one patient with SFA below the established limit in this population.…”
Section: Discussionsupporting
confidence: 89%
“…This is in line with the finding of previous studies [32]. Further, BMI was not found to be associated with outcomes of HCC patients after liver transplantation neither in present nor previous studies [51]. The necessity of evaluating subcutaneous and visceral adipose tissue on computed tomography in obese patients seems more controversial, as there was only one patient with SFA below the established limit in this population.…”
Section: Discussionsupporting
confidence: 89%
“…Similar mechanisms can be applied to the finding of a survival benefit for obese melanoma patients from the single included study. Several evidences indeed confirmed that a high BMI might be considered a surrogate marker of clinical benefit from immune checkpoint inhibitors for advanced melanoma patients 23 32 34 .…”
Section: Discussionmentioning
confidence: 85%
“…Our literature search yielded 1,892 articles, of which 203 met the inclusion criteria for our overall systematic review of the effect of obesity on cancer outcome 21,22,31,121130,32,131140,33,141150,34,151160,35,161170,36,171180,37,181190,38,191200,39,201210,40,211220,23,41,221223,4250,24,5160,25,6170,26,7180,27,8190,28,91100,29,101110,30,111120 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…[ 16 , 30 , 31 ] Further studies also describe an increased risk of death after transplantation for patients with an increased visceral‐subcutaneous fat tissue ratio, [ 32 ] an increased visceral fat area, [ 33 ] and with myosteatosis. [ 22 , 23 , 34 ] However, there are also contrary data showing that obesity does not affect survival after liver transplantation, [ 35 , 36 ] suggesting that the distinction between different fat compartments might be the clue to reliably predict patients’ outcome in different disease scenarios.…”
Section: Discussionmentioning
confidence: 99%